Limon’s earthquake in 1991: resulting reflections from the psychological work carried out by the School of Psychology of the University of Costa Rica - Sáenz-Segreda, Lorena (2021)
The article is a reconstruction of the experience in psychological support in the emergency attention process after the Limon earthquake in 1991. By making use of a qualitative research method based on construction of collective memory and experience systematization, thus the group sets up virtual meetings in which collective reconstruction of the experience, axes of systematization, lessons learned, and achievements were discussed. The systematization handles: background information, Psychology’s entrance (with the School of Psychology), and actions carried out during and after the earthquake took place. Chief reflections establish that this experience was fundamental for University of Costa Rica’s work in the emergencies and disasters field, i.e. interdisciplinary work, supporting and strengthening of their satellite campuses in topics of risk management and psychosocial support, and lastly the integration of various instances for risk management.